2013
DOI: 10.4238/2013.december.11.2
|View full text |Cite
|
Sign up to set email alerts
|

Infertility caused by male partners with genetic defects in Sichuan Province of China

Abstract: ABSTRACT. The purpose of this study was to detect chromosomal aberrations and azoospermia factor (AZF) microdeletions in male patients with reproductive problems and to summarize related clinical features to provide reliable information for evaluating prenatal and preimplantation diagnoses. A large cohort of 5083 men with various phenotypes of male infertility was analyzed via G-banding karyotyping, and Origin 8.0 was used to analyze the prevalence of abnormalities. Additionally, patients with azoospermia, oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Pylyp et al (2013) reported chromosomal abnormalities in 17% of Ukrainian patients with sperm disorders and Fu et al (2012) reported 11.55% of infertile Chinese men to have chromosomal abnormalities. The rate of chromosomal anomaly in men living in Central China was furthermore reported to be 6.84% (Liu et al, 2013) and abnormal chromosomal karyotypes were identified in 8.84% of infertile northeastern Chinese men and in 7.61% of male partners in Sichuan Province, China (Quan et al, 2013). In this study, the total prevalence of chromosomal abnormalities among the study participants was found to be 10.55% and the incidence of numerical or structural chromosomal abnormality was 7.68% (255/3319).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pylyp et al (2013) reported chromosomal abnormalities in 17% of Ukrainian patients with sperm disorders and Fu et al (2012) reported 11.55% of infertile Chinese men to have chromosomal abnormalities. The rate of chromosomal anomaly in men living in Central China was furthermore reported to be 6.84% (Liu et al, 2013) and abnormal chromosomal karyotypes were identified in 8.84% of infertile northeastern Chinese men and in 7.61% of male partners in Sichuan Province, China (Quan et al, 2013). In this study, the total prevalence of chromosomal abnormalities among the study participants was found to be 10.55% and the incidence of numerical or structural chromosomal abnormality was 7.68% (255/3319).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of chromosomal abnormality in infertile men is 2.1-19.48% (Yatsenko et al, 2010;Fu et al, 2012;Ghorbel et al, 2012;Quan et al, 2013;Ananthapur et al, 2014;Kate et al, 2014). Chromosomal defects may decrease male fertility and increase the history of female adverse fertility outcomes, e.g., recurrent spontaneous abortion or stillbirth.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of reciprocal translocation carriers is seven times higher than that of a newborn series (Ferlin et al, 2007). Additionally, the incidence of balanced reciprocal translocation is (reportedly) the highest on chromosome 1 in couples with reproductive failure (Quan et al, 2013;Zhang et al, 2015b). In this study, reciprocal translocation was identified in 82 (1.57%) infertile men, among who 23 (28.05%, 23/82) were carriers of the chromosome 1 translocation.…”
Section: Discussionmentioning
confidence: 50%
“…These effects are dependent on the specific chromosomes involved in the translocation, the locations of the breaks, and the frequency of chiasmata (Vozdova et al, 2008;Harton and Tempest, 2012;Godo et al, 2013). Previous reports indicate the involvement of balanced reciprocal translocations on chromosome 1 in male infertility and recurrent miscarriages (Tharapel et al, 1985;Quan et al, 2013;Zhang et al, 2015b,c). Chromosome 1 may harbor a critical domain whose integrity is essential for male fertility (Bache et al, 2004;Paliwal et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…As genetic studies of infertile men are usually limited to chromosomal abnormalities and YCMDs [Balkan et al, 2008;O'Flynn O'Brien et al, 2010;Quan et al, 2013;Hotaling and Carrell, 2014], there is a lack of information about the contribution of DSD to male infertility. The aim of this study was to evaluate the frequency of adult men referred to our service due to infertility who had a DSD not diagnosed during childhood or adolescence.…”
mentioning
confidence: 99%